The killer question [large type] - Hallett, Janice (Center Point Large Print, 2026)
"... A mystery that takes place at a pub's weekly trivia night, revealed through quiz categories, phone messages, and email correspondence. Sue and Mal Eastwood run an isolated rural pub called The Case is Altered where a weekly trivia game has revived its flagging fortunes--that is, until a body is found in the nearby river. Soon after, a mysterious new team arrives and shakes up the diverse field of regulars by scoring top marks in every round . . . every week. Meanwhile, Sue and Mal have a secret of their own. Before arriving here, they were caught up in a secret police operation which meant they had to leave town--and whatever happened back then seems to have finally caught up with them. Five years later, the pub lies derelict, and their nephew Dominic is determined to make a documentary about their story. What happened at this unassuming pub? And can a single question really kill?"--